Need for Technologically Non Mediated Media in a Digital Age - Challa, Ramakrishna; Vurity, Mounika; Vardhan, P Bobby (Journal of Advanced Research in Humanities and Social Sciences; Vol 8 No 3 (2021): Journal of Advanced Research in Humanities and Social Sciences, 2022)
Communication in the 21st century is canopied with digital screens. Most of the conversations be it at the workplace or in personal environments are happening through digital platforms. With growing digitalisation, the need for non-mediated media is being felt. This study is aimed at analysing the digital time of internet users and to understand their perception towards the need for non-mediated media to provide them relief from digital gadgets. The study also observes the presence of any relation between digital time of respondents and their perception towards non-mediated media as a welcome relief from digital screens. How to cite this article: Mounika V, Ramakrishna C, Vardhan PB. Need for Technologically Non Mediated Media in a Digital Age. J Adv Res Humani Social Sci 2021; 8(3): 12-15. DOI: https://doi.org/10.24321/2349.2872.202104